Terapi Komplementer Rinitis Alergi - Hafshah Hafshah (Jurnal Medika Hutama, 2021)
Allergic rhinitis is a form of hypersensitivity reaction on an atopic patient who sensitized by a specific allergen before. Allergic rhinitis symptoms are sneezing, nasal pruritic, airway obstruction, and rinorrhea. In Indonesia, the prevalence number of rhinitis allergic reach 1.5 – 12.4%. Despite it’s not directly related to the cause of death, allergic rhinitis affects the quality of life, sleep, exercise tolerance, productivity, and social function of its sufferer. Complementary therapies is an additional therapy that use any certain modality which not included in conventional drugs. Complementary therapies aimed to increase the health level. Drugs, herbs, or methods which can be used in complementary therapy are honey, royal jelly and propolis, probiotic, ginger, vitamin D, vitamin E, and acupoint herbal plaster. Complementary therapies can be used in rhinitis allergic treatment beside of conventional therapy.